"Russell body" gastritis: A case report - ÇELİKEL, ÇİĞDEM; KAYA, HANDAN (My University, 2010)
Our case was a 50-year-old female who presented at the outpatients department with dyspeptic symptoms. Microscopical examination of mucosal samples from the corpus and antrum showed widespread Helicobacter pylori within the superficial mucus network, marked neutrophilic cryptitis, widespread reactive/regenerative crypt hyperplasia, intestinal metaplasia, and increased lymphoplasmocytoid cells and plasma cells full of immunoglobulin in the lamina propria. Immunohistochemical staining showed the plasma cells to be CD3 (-), CD20 (-), CD79a (+), CD45 (+), Kappa (+), and Lambda (+). It is possible for a dense accumulation of Russell bodies to be observed on a background of H. pylori taking into account that Russell bodies contain immunoglobulin aggregates and side products of immunoglobulin synthesis. However, there are only a limited number of articles evaluating this aspect. We present a case to contribute to the few articles on Helicobacter gastritis characterized by an inflammatory reaction rich in ‘’Russell’’ bodies

Olgumuz dispeptik yakınmaları nedeni ile kliniğe müracaat eden 50 yaşında kadın hastadır. Antrum ve korpusa ait mukoza örneklerinin mikroskopik incelemesinde yüzey mukus ağı içinde yaygın helicobacter pylori, belirgin nötrofilik kriptit, yaygın reaktif/ rejeneratif kript hiperplazisi, intestinal metaplazi, lamina propriada içleri immünglobülin ile dolu plazma hücreleri ve lenfoplazmositer hücre artışı izlenmiştir. Olguya uygulanan immünhistokimyasal boyalarda immünglobülin ile dolu plazma hücrelerinin CD3 (-), CD20 (-), CD79 a(+), CD45 (+), Kappa (+), Lambda (+) olduğu saptanmıştır. Russell cisimciklerinin immünglobülin agregatları ve immünglobülin sentezinin yan ürünleri içerdiği düşünülürse H.pylori zemininde Russell cisimciklerinin yoğun olarak saptanması olasıdır. Ancak günümüze değin bu açıdan değerlendirilmiş sınırlı sayıda yayın bulunmaktadır. Literatürde ‘’Russell’’ cisimciklerinden zengin inflamatuar reaksiyonla karakterize Helikobakter gastritinin nadir bildirilmiş olması nedeni ile olgumuz sunulmuştur.
“Russell body” gastriti: Olgu sunumu
Keywords: Tıp; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Surgery Medicine Sciences; Pathology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; PATOLOJİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); PATHOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Patoloji ve Adli Tıp; Histoloji; Biyokimya (tıbbi); Pathology and Forensic Medicine; Histology; Biochemistry (medical); Russell body; Gastritis; Helicobacter pylori; Mott cells; Russell body; Gastrit; Helikobakter pilori; Mott hücresi; Russell body; Gastritis; Helicobacter pylori; Mott cells